Novel green treatment for functional surfaces. (Research'eu results magazine)
EU researchers have introduced a new plasma technique for thermochemical treatment that improves the corrosion and wear resistance of surfaces. Medical implants, fuel cell plants, solar panels and tiny mechanical devices will be the recipients of some good fortune if the technology is exploited to create innovative products.